Empowerment of Pondok Mimbo Coastal Communities in an Effort to Increase Awareness of Population Administration and Fisherman Independence - Dimas Imaniar; Erna Agustina (Airlangga University, 2021)
AbstractPondok Mimbo, Sumberanyar Village is one of the largest fishing villages in Situbondo Regency after Kilensari Village, Panarukan District. The people of Pondok Mimbo are mostly indigenous people whose lineage comes from Madura, East Java. Pondok Mimbo Village is a mainstay area of Situbondo Regency which has an important role in realizing Situbondo Regency as a marine area on the north coast of Java. This study finds the right empowerment model for the coastal community of Pondok Mimbo and analyzes efforts to increase awareness of population administration and the independence of fishermen in Pondok Mimbo. This research is included in descriptive qualitative research with a sociological approach, or in public administration research commonly referred to as applied normative/empirical normative. The empowerment model which aims to build the independence of the fishermen of Pondok Mimbo can be implemented with the cooperation and participation of the community. There needs to be a synergy between the role of the government, both village officials and other relevant agencies, NGOs or related companies, campuses, and the fishing communities themselves. There are supporting factors and inhibiting factors that must be considered and solutions are sought. Supporting factors include the development of the concept of awareness in carrying out all kinds of activities in accordance with the existing population administration, tourism potential and fishery production, active village officials, and the readiness of human resources to motivate themselves and receive assistance and various trainings. The inhibiting factors include limited capital, natural factors, infrastructure, lack of interest in tourism, purchasing power and interest in water games, non-routine income, workers' salaries that are less than the minimum wage, human resources, and lack of awareness of the population. administration, legal aid, and legal protection.Keywords: empowerment, awareness, independence of fishermen.